KONSTRUKSI HUKUM POLIGAMI DALAM PEMIKIRAN K.H. HUSEIN MUHAMMAD: TELAAH NORMATIF-KONTEKSTUAL - Mutho`, Izzul (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This article discusses the thoughts of K.H. Husein Muhammad on polygamy in Islam, focusing on the legal construction and argumentative foundations behind his critical stance toward the practice. In contrast to the majority of classical scholars who permit polygamy broadly, K.H. Husein views justice as an absolute requirement that is extremely difficult to fulfill in practice. This study aims to analyze the legal construction and fundamental reasoning of K.H. Husein Muhammad regarding polygamy in Islam. It employs a normative-contextual approach using library research and direct interviews as methods of data collection, with descriptive-qualitative analysis. The findings indicate that K.H. Husein Muhammad considers polygamy not as a normative teaching recommended in Islam, but rather as a rukhṣah (legal concession) for certain situations. In the context of modern society, he argues that polygamy tends to result in injustice—especially toward women—and contradicts the principles of maqāṣid al-sharī‘ah and the legal maxim sad al-dharī‘ah. Therefore, he concludes that the permissibility of polygamy may shift to being discouraged (makrūh) or even prohibited (ḥarām) if it fails to uphold substantive justice. His thought reflects a form of progressive ijtihād that prioritizes contextual interpretation of religious texts and advocates for reform in Islamic family law that promotes social justice and gender equality.